Representation of Political Ideology in Advertising: Semiotics Analysis in Indonesia Television - Briandana, Rizki (International Journal of English Literature and Social Sciences (IJELS), 2019)
Abstract: This study aims to analyze the meaning and symbols in the political party's advertising on Indonesian television. Towards the presidential election, political parties use advertising as a means of marketing communication. As the form of persuasive information, the Perindo Party's television advertisement was analyzed by using Charles Sanders Pierce's Triangle of Meaning for the semiotic method. According to Pierce, the signs in the picture can be classified into the types of signs in semiotics. Pierce divides the signs into: icons, indixes and symbols. The research results show that Perindo Party's Nationalist ideology upholds pluralism in Indonesia. It has special message that Indonesia does not belong to a particular religious, cultural or racial group. The meaning of contemporary nationalism in this advertisement is tried to raise particularly for young people with the aim of developing potential for a better life.